The Scottish police caution: do individuals with intellectual disabilities understand a verbally presented police caution, and can comprehension be improved?. Issue 1 (2nd January 2021) - Rendall, Michael; MacMahon, Ken; Kidd, Bruce
Abstract : This study considers comprehension of the Scottish police caution amongst people with an intellectual disability ( n = 30). It applies techniques to the caution that are suggested to increase its 'listenability', to examine whether this could be a successful method of improving understanding. These techniques include providing instructions, further explanations and listing information. Half of the participants were assessed using the original version and half the modified version. Participants were assessed using an abbreviated IQ assessment, a measure of working memory and measure of state anxiety to consider potential predictors of performance. The modified version did not improve performance, with no participants judged to have adequate understanding in either version.